Tactical interventions in libraries - Karen Munro (Journal of New Librarianship, 2017)
“Tactical urbanism” is a catchphrase describing a wide range of ways in which ordinary people improve their neighborhoods, through interventions ranging from seed - bombing vacant lots to building impromptu parks. Tactical interventions are cheap, quick, and accessible to everyone. Libraries can adopt a tactical approach by consciously leveraging lightweight, experimental, iterative, and small - scale projects in support of larger strategies. This column will outline the characteristics ofsuccessful tactical interventions, and describe two real - world library projects that demonstrate the effectiveness of this approach.